A Factorial Survey Study on the Influence of Advertising Place and the Use of Personal Data on User Acceptance of Facebook Ads. (June 2017) - Broeck, Evert Van den; Poels, Karolien; Walrave, Michel
Advertisements on social networking sites are typically unrequested messages placed in between the user-generated content. What makes users accept these ads (or not)? A factorial survey was conducted to uncover the impact of different factors related to the use of personal data (e.g., sensitivity of personal data) and advertising place (e.g., ad location) of Facebook ads on user acceptance (i.e., fairness and appropriateness) of the advertisement. Placement of the advertisement was the only factor to significantly affect user acceptance. Moreover, the effect of ad placement largely depended on the degree of involvement with the advertised product. Among low-involved subjects, sidebar ad placement was better accepted. Moreover, the influence of ad placement on user acceptance was fully mediated by perceived intrusiveness of the ad. This indirect effect was not significant in the high-involved subgroup, where message stream placement was better accepted. Implications for targeting advertising on Facebook are discussed.